Effects of Urea Removal on the Stable Isotopes Î´13C and Î´15N in Rays from the Coastal Waters of Peninsular Malaysia - Maizah Mohd Abdullah; Wei Yien Lua; Roslanzairi Mostapha; Zalina Bashir; Mohd Naimullah; Sukree Hajisamae; Fazrul Hisam (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research